الزمن المطلق في الرواية العربية وأثره في التلقي - حمود، زينة حمزة شاكر (جامعة بابل, 2015)
تشكل هذا البحث عبر مسار اشتغالنا في رصد تجليات الزمن المطلق لنصين روائيين، من خلال تقصي الخصائص النوعية للزمن في الخطاب الأدبي والتي تصلح لآن تشكل ظاهرة فنية من خلال الكشف عن التمظهرات الزمنية بلغة كثيفة ورؤية صوفية في تشكل المنجز الروائي وكان أن اثمرت الدراسة عن بعض النتائج 1-الزمن‏ المطلق زمن يعتمد راهنية الوعي ينأى عن الانضواء تحت معيار محدد انه زمن تحدده الخبرة الإنسانية ووعي الأنسان بذاته فيتلاشى التسلسل والمنطق. ويخضع لقوانين العاطفة والخيال وتكريس المشاعر الإنسانية وإخضاعها لسلطة الروح 2-للنص الروائي جماليته من حيث ترسم نعوت ذات مرجعيات انثروبولوجية ودينية منها استذكار استشهاد سيدنا الحسين (عليه السلام)، وقصة أهل الكهف، والنبي موسى، والخضر، عليهما السلام وعبد الناصر، وشهرزاد، عززت بها الذات (نوستولوجيتها) إلى الماضي ممثلة بخصائص المكان وجزءا من جغرافيته الثقافية. ٣-في‏ ركون الروائيين إلى زمن أسطوري سعى الروائي إلى غايتين الأولى، تأمل الظلم والعدالة في أصولهما الشفافة الأولى واشتقاق الأزمنة القادمة من الزمن الأصلي فبعد أن غدا الحاضر ثقيل ومهم الإجابة اجبر السائل المغترب على ترحيل سؤاله إلى الماضي التماسا للوضوح واستنكارا للحاضر، كما لو كانت الأسطورة وهي زمن الحلم قائمة في حاضرتوهم التحرر من الأساطير في المجاورة بين القرآن الكريم وألف ليلة وليلة حيث الأجواء العجائبية ٤-النص‏ الأدبي بنية من التحولات والأنماط على أثر تجدد التلقي، هو محاورة بين مستويات خطاب متعددة لا تخضع لزمن محدد بل هو زمن دينامي يتغير بتغير أنماط الرواة وقراءة المتلقي. This research has evolved through investigating the dimensions of absolute time in two narrative texts, by pursuing the qualitative features of time in the literary discourse, which can be an artistic phenomenon through uncovering time variations in forming the narrative achievement in condense language and lively look. The study has arrived at the following conclusions: 1-Absolute time depends on consciousness and refuses any withdrawal under any criterion. It is specified by the human experience without attention by order or logic. It is subject to the laws of emotion, imagination and the authority of the soul. 2-A narrative text has its own beauty as certain qualities are drawn with anthropological and religious references, like remembering the martyrdom of al- Husain (peace be upon him), the story of the cave inhabitants ,prophet Moses and al- Khidhir (peace be upon them), abdul-Nasir and Shahrazaad, which return us nestologically to the past representing the qualities of the place and part of the educational geography. 3-In relying on legendary time, anarrator aims at viewing tyranny and justice in their transparent origins and deriving thw coming times from the original time. Because the present has become too heavy and too ambiguous for answering , one is now obliged to transfer one’s question to the past for the sake of clarity and reusal of the present , as if the dream, is standing in the present and is suggesting in the holy Quran and One Thousand and One Nights, where we find the wonderful astomspheres. 4-A literary text is a structure of changes and types on the basis of the renewal of receiving, which is a compromise among the various levels of discourse which do not submit to a specific time. It is a dynamic time which varies with the changes of the models of narrators and the receivers.
Keywords: الروايات العربية -- نظرية التلقي -- الفضاء الزمني -- الأدب العربي